Removal of total lipids and fatty acids from sunflower oil factory effluent by UASB reactor - Saatci, Y; Arslan, EI; Konar, V (Elsevier Sci Ltd, 2003)
In this study wastewaters of a sunflower oil factory in Elazig (Turkey) were investigated in a pilot-scale mesophilic upflow anaerobic sludge blanket (UASB) reactor by determination of removal of total lipids (TL) and fatty acids (FA). The removal efficiencies of TL and FA (linoleic, oleic, myristic, palmitic, stearic, arashidic, behenic and other FA) were above 70% at organic loading rates (OLR) between 1.6 and 7.8 kg COD/m(3) d and at optimum hydraulic retention times of 2.0 and 2.8 day. The conversion rate of removed COD to methane was between 0.16 and 0.354 m(3) CH4/kg COD. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: total lipid; fatty acids; methane; UASB; sunflower oil factory; wastewater